Maintaining the protective function of mountain forests under climate change by the concept of naturalness in tree species composition - Scherrer, Daniel; Allgaier Leuch, Barbara; Fischer, Christoph; Frehner, Monika; Wohlgemuth, Thomas (Frontiers in Forests and Global Change, 2023)
In Swiss mountain areas, the protective function of forests is the predominant ecosystem service having high cultural and economic significance. It is assumed that natural forests or close-to-natural forests, i.e., forests being in the equilibrium with environmental conditions are the most resilient and resistant in regard to disturbances and hence best protecting people and assets on the long run. Here, we estimated the naturalness of the tree species composition by comparing Swiss National Forest Inventory (NFI) data with current and future potential Natural forest Site Types (NST). Based on this analysis, we identified species that are under or over-represented in protective mountain forests and derived the subsequent potential for management interventions. The urgency of management interventions is expected be small if all predominant tree species of the idealized potential natural forests are present and only their relative portions in the stand need adjustment. In contrast, interventions are advisable, if predominant tree species of the current and future potential natural forests are absent. Based on NFI data, the tree species composition of 47% of the protective mountain forests were classified as “natural” or “close-to-natural,” while the remaining 53% were classified as “not natural” or “partly natural.” Norway spruce [Picea abies (L.) H. Karst.] and European larch (Larix decidua Mill.) were the two most over-represented species under current and even more so under predicted future climatic conditions. To date, silver fir (Abies alba Mill.) and European beech (Fagus sylvatica L.) were the two species most frequently absent in protective mountain forests, in which they should prevail. Apart from European beech, the most prominent increase in prevalence is predicted for oak (sessile oak and pubescent oak; Quercus petrea Liebl., Q. pubescens Willd.) and small-leaved lime (Tilia cordata Mill.). These species were currently missing from more than 75% of the stands, in which they are expected to be dominant under future conditions. Our analysis indicates the need to transform tree species compositions of protective mountain forests to optimize fitness under future climates. Some of these transformations will take place naturally, incited by disturbances, others—the majority of them—will need active management interventions.